2021
DOI: 10.1155/2021/8862399
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Acupressure on Low Back Pain: A Systematic Review and Meta-Analysis

Abstract: Objectives. To evaluate the effectiveness and safety of acupressure on low back pain (LBP). Methods. We searched 7 electronic databases and 2 trial registries through December 28, 2020. Randomized controlled trials (RCTs) of acupressure on LBP were considered for meta-analysis with Revman 5.3 and Stata 15.0 software. Methodological quality was evaluated using the Cochrane Collaboration’s tool. Trial sequential analysis (TSA) was used to quantify the statistical reliability. HETRED analysis and GRADE were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 22 publications
(18 reference statements)
0
32
1
1
Order By: Relevance
“…Currently, there is no systematic review on acupressure for OA. In comparison to prior systematic reviews on acupressure for musculoskeletal conditions including low back pain [10,12], neck pain syndrome [16], and musculoskeletal pain [46], our results are found to be only partially consistent with their findings on acupressure showing positive effect in pain reduction. Our pooled results showed that acupressure has superior effects in reducing pain as a complementary intervention to conventional intervention, but not as sole intervention.…”
Section: Agreements and Disagreements With Other Studies Or Reviewscontrasting
confidence: 77%
See 1 more Smart Citation
“…Currently, there is no systematic review on acupressure for OA. In comparison to prior systematic reviews on acupressure for musculoskeletal conditions including low back pain [10,12], neck pain syndrome [16], and musculoskeletal pain [46], our results are found to be only partially consistent with their findings on acupressure showing positive effect in pain reduction. Our pooled results showed that acupressure has superior effects in reducing pain as a complementary intervention to conventional intervention, but not as sole intervention.…”
Section: Agreements and Disagreements With Other Studies Or Reviewscontrasting
confidence: 77%
“…Acupressure has been used for various purposes. Previous systematic reviews have investigated the efficacy or the impact of acupressure as a sole intervention on pain [11], low back pain [10,12], labor or labor pain [13][14][15], neck pain syndrome [16], sleep quality, or sleep disorders [17][18][19], promoting the health of older adults [20], respiratory allergic diseases [21], postoperative gastrointestinal symptoms [22], chemotherapy-induced nausea and vomiting [23], primary dysmenorrhea [24][25][26], anxiety [27], neurological disorders [28], and symptom management [29][30][31]; and other reviews considered acupressure as a complementary intervention with acupuncture on cancer pain [32], cancer-related fatigue [33], weight reduction [34], uremic pruritus [35], premenstrual syndrome [36], and labor pain [37].…”
Section: Introductionmentioning
confidence: 99%
“…In this review, manual therapies that showed significant improvement in some outcomes of the quality of life in COPD patients were acupressure and tuina belonging to Eastern manual therapy. These therapies may not only affect lung function or exercise capacity in COPD patients but may also help improve other disturbing symptoms, including pain [ 49 ], insomnia [ 50 , 51 ], and fatigue [ 50 ], as seen in previously published studies, thereby contributing to the improvement in the quality of life of COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…As a widely used complementary and alternative therapy, manual therapy (MT) is performed by the hands on external areas of the body, which can affect the internal physiological state [26]. In China, Tuina is a traditional style of MT that involves pressing, pinching, and kneading the body [27] and has demonstrated positive effects for treating LBP in clinical practice [28][29][30]. However, there have been few studies on the effects of MT on tissue degeneration beyond pain relief, although an association has been shown between LBP and age-related IVD degeneration [31].…”
Section: Introductionmentioning
confidence: 99%